Taking Hold of Reality: White Protestant Theology and Racism at the End of White Christian America - Norris, Kristopher (Journal of religion & society. Supplement, 2020)
This essay places twentieth century white U.S. Protestant theology in conversation with the liberation theologies of Ignacio Ellacuría and James Cone. Drawing on Ellacuría’s belief that theology begins with “taking hold of reality,” it demonstrates the ways that the most prominent threads in white U.S. Protestant theology and ethics failed to take hold of the reality of racism, neglecting those Cone calls “the crucified people” in America – African Americans. It then argues that black liberation theology supplies the perspective and methodology – at least in U.S. Protestant theology – for following Ellacuría’s proposal. The Black theology of Cone, in light of Ellacuría’s concerns, offers a different model of doing theology in the U.S. context, one that corrects for the blindnesses and abstractions in conventional white Protestant theology.